Стихотворения - Батюшков Константин Николаевич (Классики и современники, 1987)
Экземпляры: аб (20190621) / Инвентарный номер: 53868 / Цена: 20.00 / Сис.шифр: Р1 / Авт.знак: Б 28 / ГРНТИ: 17.82 / ББК: 84 (2 Рос-Рус)1